Simulations on W impurity transport in the edge of EAST H-mode plasmas. (26th October 2018) - Wang, Fuqiong; Zha, X J; Duan, Y M; Mao, S T; Wang, L; Zhong, F C; Liang, Y.; Li, L; Lu, H W; Hu, L Q; Chen, Y P; Yang, Z D
Abstract: This paper provides an investigation of the production/transport properties of W impurity in the edge of experimental advanced superconducting tokamak (EAST) H-mode discharges with upper-single-null configurations by using DIVIMP Monte-Carlo code. The background plasmas are provided by SOLPS5.0 calculations. Firstly, to address the detailed dependence of W impurity behaviors on plasma conditions in the scraped-off layer (SOL)/divertor region of EAST, two pre-edge localized mode (ELM) cases with divertor plasmas in high-recycling and partially-detached regimes, respectively, are considered and compared. It is found that, due to the competitions between the thermal and friction forces (FFs), in the high-recycling case, large quantities of W impurities are transported to the upstream; while in the partially-detached case, most of the W impurities are located near the inner and outer divertors. Furthermore, the W core contamination in type-I ELMy H-mode plasmas of EAST has been estimated by the DIVIMP-SOLPS5.0 simulations, without the consideration of the release of W impurity from the core due to ELMs. During the ELM, simulations exhibit the low-recycling regime of divertor plasma, and high (several hundred eV) target plasma temperatures together with low SOL collisionality ( ν S O L *  ∼ 1–3), lead to an order of magnitude increase in the W core contamination rate. However, in the ELM-recovering phase, with the decrease (increase) of divertor plasma temperature (density), significant increase of divertor retention is obtained due to the remarkable increase of FFs on W ions. Besides, intra-ELM phase approximately contributes to more than 50% of the total W core contamination per an ELM cycle. This work represents a step toward a deeper understanding of the W impurity production/transport in EAST H-mode discharges.